Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12893-020-00867-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Postoperative Outcomes in Pediatric Surgery Patients in Rural Ghana

Abstract: Background/Purpose Perioperative complications cause significant pediatric morbidity and mortality in low- and lower middle -income countries. This study investigates factors associated with prolonged length of stay, 90-day readmission and in-hospital mortality among pediatric patients at Eastern Regional Hospital (ERH) in Ghana. Methods This is a retrospective review of perioperative morbidity and mortality in children < 18 years at ERH in Koforidua, Ghana. All pediatric surgeries performed between Janua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
4
4
0
1
Order By: Relevance
“…The current study found that children admitted for a trauma-related reason were more likely to have an unfavorable management outcome. This is consistent with the study done in Ghana [ 24 ], Nigeria [ 18 ], and Ethiopia [ 25 ]. This could be explained by the fact that trauma cases are more likely than other admissions to have complications like infection, hemorrhage, respiratory failure, renal failure, and sepsis, which complicate surgical cases by delaying wound healing and recovery time [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study found that children admitted for a trauma-related reason were more likely to have an unfavorable management outcome. This is consistent with the study done in Ghana [ 24 ], Nigeria [ 18 ], and Ethiopia [ 25 ]. This could be explained by the fact that trauma cases are more likely than other admissions to have complications like infection, hemorrhage, respiratory failure, renal failure, and sepsis, which complicate surgical cases by delaying wound healing and recovery time [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to this study, children who received surgical management were almost twice more likely to be discharged with unfavorable management outcome when compared to their counterparts. This finding was supported by a study done in Ghana [ 24 ]. This could be explained by the fact that children who have had surgery are more likely to experience complications such as postoperative infection, hemorrhage, and wound dehiscence, all of which complicate the postoperative recovery phase.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Malnutrition effects immunological function, tissue healing, and may result in sub‐optimal postoperative outcomes. Anaemia, associated with malnutrition, malaria, and HIV present additional difficulties especially when if blood donation is required [25].…”
Section: Paediatric Surgical Management In Ssamentioning
confidence: 99%
“…The number of cardiac arrests described was 150, but the correct number of cardiac arrests in children was 50, as described in the article. Peiffer et al [ 15 ]. The accurate year of publication is 2020, not 2018.…”
mentioning
confidence: 99%